Weighing in on Adipogenesis - Nunn, Elizabeth R.; Shinde, Abhijit B.; Zaganjor, Elma (Frontiers in Physiology, 2022)
Obesity is a growing health concern worldwide because of its contribution to metabolic syndrome, type II diabetes, insulin resistance (IR), and numerous cancers. In obesity, white adipose tissue (WAT) expands through two mechanisms: increase in adipocyte cell number by precursor cell differentiation through the process of adipogenesis (hyperplasia) and increase in existing mature adipocyte cell size (hypertrophy). While hypertrophy is associated with the negative effects of obesity on metabolic health such as inflammation and lipotoxicity, adipogenesis prevents obesity-mediated metabolic decline. Moreover, in metabolically healthy obesity adipogenesis is increased. Thus, it is vital to understand the mechanistic basis for adipose expansion to inform novel therapeutic approaches to mitigate the dysfunction of this tissue and associated diseases. In this mini-review, we summarize recent studies on the regulation of adipogenesis and provide a perspective on targeting adipogenesis as a potential therapeutic avenue for metabolic disorders.